Pendampingan dan Pelatihan Pemanfatan Sampah Popok Bayi di Desa Karangtalun Kecamatan Kalidawir, Tulungagung - Widodo, Wimbuh Tri; Kristianto, Sonny; Putri, Rury Eryna; Aprilia, Chatrina; Rahmadani, Anindita Mutiara; Martha, Rahma Diyan; Danar, Danar; Kumalasari, Nurul Chamidah (Universitas Pahlawan Tuanku Tambusai, 2025)
Environmental issues caused by baby diaper waste have become a major concern in Karangtalun Village, Tulungagung, due to the low public awareness of its impact. This community service aimed to enhance residents’ knowledge and skills in processing diaper waste into useful planting media. The methods applied included education, training, and demonstrations. Residents were educated on the environmental impact of waste and trained to produce planting media from used baby diapers using the kokedama technique. The results showed improved public understanding of waste management and growing interest in utilizing waste as a business opportunity. This activity also had a positive impact on environmental cleanliness and local economic potential. These findings demonstrate that community-based waste management initiatives are effective in improving environmental quality and community welfare.